3-Phase bone imaging and SPECT in the follow up of patients with allogenic vascularized knee joint transplants - Manthey, N., MD; Kirschner, M. H., MD; Neriich, A., MD; Hofmann, G. O., MD; Tatsch, K., MD; Hahn, K., MD (Nuklearmedizin - NuclearMedicine, 2001)
Vascularized allotransplantation of knee joints under immunosuppression is a novel approach in orthopedic surgery. During the postoperative course immunosuppressive management depends on perfusion and viability of the graft. Aim: Evaluation of different diagnostic tools in regard to their usefulness and reliability to provide information about microvascularity and viability of vascularized knee joint allografts. Methods: Four patients with allogenic knee joint transplants were studied up to 26 months after transplantation with 3-phase bone scans and SPECT. The results were compared with duplex sonography, angiography, and histology. Results: Two cases without complications were characterized by adequate perfusion in duplex sonography, angiography and early bone scans. Late bone scans demonstrated increased bone metabolism of the transplant. Corresponding biopsy revealed viable bone cells. In one case with partial thrombosis and one case with complete thrombosis of the transplant vessels rapidly decreasing or missing perfusion was detected by duplex sonography, angiography, and bloodpool scintigraphy. Late bone scans showed reduced or absent bone metabolism. Biopsy demonstrated necrotic bone tissue. Due to the advantage of a tomographic technique SPECT allowed a more reliable assessment of graft viability as compared to planar imaging. Conclusion: Our findings confirm bone scintigraphy as a valuable diagnostic tool in patients with allogenic vascularized knee joint transplants. In contrast to other diagnostic approaches, scintigraphy provides reliable information on both viability and perfusion of the transplant within a single noninvasive clinical investigation.
Keywords: Bone scintigraphy; vascularized bone graft; allogenic knee joint transplantation; viability; microcirculation